A short peptide from sAPPα binding to BACE1-APP action site rescues Alzheimer-like pathology. (23rd January 2022) - Lai, Xia; Hu, Jie; Liu, He; Lan, Ling; Long, Yan; Gao, Xia; Deng, Juan
Highlights: A short peptide derived from sAPPα rescues behavioral deficits of an AD mouse model. This short peptide ameliorates AD-type pathologies by modulating BACE1 activity. This short peptide may be a novel, safe and effective BACE1 inhibitor for the treatment of AD. Abstract: Amyloid β-peptide (Aβ) is the driven force of Alzheimer's disease (AD), and reducing Aβ production could be a potential therapeutic strategy for AD. sAPPα appears to have the ability to specifically inhibit β-cleavage of APP without inhibiting BACE1 completely, direct administration of sAPPα may not be clinically applicable due to the low permeability of blood–brain barrier (BBB). In this study, we investigated the neuroprotective effects of a short peptide generated from sAPPα, which could specifically bind to BACE1 at the BACE1-APP action site. We found that this peptide significantly reduced Aβ production both in vivo and in vitro, thus further attenuated Aβ deposition, Tau hyperphosphorylation, neuroinflammation et al. and rescued behavioral deficits. Therefore, this short peptide may hold promise for the treatment of AD due to its neuroprotective effects, low molecular weight to cross BBB, and less safety concerns. The anti-neurodegenerative capacity of sAPPα may not result solely from direct inhibition of BACE1.